1992
DOI: 10.1002/abio.370120613
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of furfural to furfuryl alcohol by saccharomyces cerevisiae

Abstract: Biotransformation of furfural by Saccharomyces cerevisiae 354 was performed in a sugar cane molasses medium containing salts. The furfural added was rapidly reduced to furfuryl alcohol until a final addition of 3%, without inhibition in the cells growth. An efficient conversion of 96% was obtained by feeding 6 g · l−1 every 6 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 4 publications
2
32
0
2
Order By: Relevance
“…The in vitro activity for furfural reduction by a The conversion rates were calculated based on consumption of furfural or HMF during the feeding of hydrolysate. The in vitro furfural-and HMF-reducing activities were measured as described previously (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro activity for furfural reduction by a The conversion rates were calculated based on consumption of furfural or HMF during the feeding of hydrolysate. The in vitro furfural-and HMF-reducing activities were measured as described previously (23).…”
Section: Resultsmentioning
confidence: 99%
“…Strains of S. cerevisiae exhibit significant differences in fermentative capacity and tolerance to lignocellulose-derived inhibitors (11). The tolerance to aldehyde compounds is most likely due to the ability of microorganisms to convert these compounds to the corresponding less inhibitory alcohols (20,23). Dilute-acid hydrolysates are often strongly inhibiting and cannot be fermented in batch mode, but they may be fermented by S. cerevisiae without prior detoxification in fed-batch mode (13,14,21).…”
Section: -Hydroxymethyl Furfural (400 Mu/mg Protein During Fed-batch mentioning
confidence: 99%
“…HMF and furfural could be consumed during yeast fermentation, while the rate of furfural consumption was a little faster. Furfural could be reduced by yeast cells to furfuryl alcohol during fermentation and cause a lag-phase in the ethanol formation but it does not affect the final ethanol yield [28]. The minimum concentration of furfural and HMF that could be tested was 0.2 g/L in the HPLC system used in this study.…”
Section: Fermentationmentioning
confidence: 99%
“…Previous studies have shown that in most cases, furfural can be converted by yeast to furfural alcohol (12,30). Sometimes furoic acid (64), furoin and furil (47), and acyloin products (28,61) can also be detected in the medium under different sets of cultivation conditions. The genetic mechanisms involved in furfural tolerance have been investigated by screening an S. cerevisiae disruption library to find potential relative genes (18).…”
mentioning
confidence: 99%